2016
DOI: 10.1097/pcc.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Children and Young Adults Who Received Tracheostomies or Were Initiated on Long-Term Ventilation in PICUs*

Abstract: Objectives To characterize patients who received tracheostomies for airway compromise or were initiated on long-term ventilation for chronic respiratory failure in pediatric intensive care units (PICU), and to examine variation in the incidence of initiation, patient characteristics, and modalities across sites. Design Retrospective cross-sectional analysis. Settings Seventy three North American PICUs that participated in the Virtual Pediatric Intensive Care Unit Performance System. Patients PICU patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 33 publications
6
41
0
3
Order By: Relevance
“…Cancelhina et al reported that 7.4% of non‐invasive patients transitioned to transtracheal ventilation, and Amin et al reported that 7.6% of patients requiring transtracheal ventilation had previously required non‐invasive respiratory support. The median age of index discharge and bimodal distribution of ages of our cohort was similar to that reported in Edwards et al, Chatwin et al, and Amin et al and is consistent with the pathophysiology of chronic respiratory failure . This study augments previous ones by being multi‐institutional, concentrating on transitions to transtracheal ventilation (as opposed to mortality), and providing granular data on multiple disorders associated with chronic respiratory failure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cancelhina et al reported that 7.4% of non‐invasive patients transitioned to transtracheal ventilation, and Amin et al reported that 7.6% of patients requiring transtracheal ventilation had previously required non‐invasive respiratory support. The median age of index discharge and bimodal distribution of ages of our cohort was similar to that reported in Edwards et al, Chatwin et al, and Amin et al and is consistent with the pathophysiology of chronic respiratory failure . This study augments previous ones by being multi‐institutional, concentrating on transitions to transtracheal ventilation (as opposed to mortality), and providing granular data on multiple disorders associated with chronic respiratory failure.…”
Section: Discussionsupporting
confidence: 92%
“…Patients were included in this study if they had one or more inpatient admissions during the study period, had a chronic condition that is associated with chronic respiratory failure, and were discharged using non‐invasive respiratory support to home or to a non‐acute care facility (eg, chronic care facility). Chronic conditions associated with chronic respiratory failure were identified using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9) codes (Supplementary Table S1) based on previous literature and by consensus of study investigators . Because our population of interest was patients with chronic respiratory failure, patients were excluded if they had an ICD‐9 code for obstructive sleep apnea or upper airway obstruction in the absence of a chronic respiratory failure diagnosis .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, LOS analyses were repeated using only this patient sub-group, for the subgroup of sites with data that allowed identification of patients using chronic ventilation via tracheostomy[15]. For this analysis, sites with IMCUs that accepted/transferred PICU patients on chronic ventilation were compared to sites with an IMCU that did not accept such patients combined with sites without an IMCU.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent retrospective analysis of 73 North American pediatric ICUs reported that among 115,437 admitted pediatric ICU patients between 2009 and 2011, 1.37% (1,583 subjects) received a new tracheostomy during that admission, and 0.6% (168 subjects) had a tracheostomy already in place. 38 The majority of children in this study had complex chronic conditions that contributed to their airway compromise or chronic respiratory failure, and most tracheostomy placements were initiated during unplanned pediatric ICU admissions and after acute/acute-on-chronic critical illness. Elective tracheostomy is rare in the pediatric setting.…”
Section: Timing Of Tracheostomy In Childrenmentioning
confidence: 99%